Complexes of Cobalt(II), Nickel(II) and Copper(II) with an Ambivalent Schiff Base Ligand
Condensation of 1-phenyl-1,2-proparndione-2-oxime with 1,2-diaminobenzene in an ethanolic medium yields a Schiff base ligand, bis-(1-phenyl-2-hydroxyimino-1-propylidene) 1,2-diaminobenzene, H2L. A number of complexes of the types [ML] [M = Co(II), Ni(II), Cu(II